Direct rapid prototyping from point cloud data without surface reconstruction. Issue 3 (4th May 2018) - Yuan, Tianyun; Peng, Xiaobo; Zhang, Dongdong
ABSTRACT: To save cost and manufacturing time, prototyping technology is increasingly playing an irreplaceable role in the industry. Rapid prototyping and reverse engineering are two major technologies that meet the demands of the development. The existing approaches of directly prototyping a physical object involve various complex processing steps, i.e. reconstructing CAD model from the scanned point data, and/or STereoLithography (STL) model generation. However, such processes require professional knowledge and skills, and are laborious and far from automatic. This paper introduces a direct prototyping system, which automatically print the object from scanned point cloud. Neither a CAD model nor a STL model is created in the proposed system. In the proposed system, the two-dimensional (2D) contours in each printing plane is generated by intersecting the printing plane and Moving Least Square (MLS) surface. The proposed system simplifies the whole workflow by integrating the point-cloud projecting process, printing path generating process and 3D printing process. A user-friendly interface is developed to streamline the process. GRAPHICAL ABSTRACT: